2021
DOI: 10.1002/anie.202108540
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Ultraviolet Organic Light‐Emitting Diode Enabled by High‐Lying Reverse Intersystem Crossing

Abstract: Ultraviolet (UV) organic emitters that can open up applications for future organic light-emitting diodes (OLEDs) are of great value but rarely developed. Here, we report a highquality UV emitter with hybridized local and charge-transfer (HLCT) excited state and its application in UV OLEDs. The UV emitter, 2BuCz-CNCz, shows the features of low-lying locally excited (LE) emissive state and high-lying reverse intersystem crossing (hRISC) process, which helps to balance the color purity and exciton utilization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 60 publications
1
73
0
Order By: Relevance
“…With this in mind, many HLCT-based deep/ pure blue materials have been developed recently. [29][30][31][32][33][34][35][36][37][38][39][40][41][42] However, most of these emitters were utilized in OLED via vacuum deposition method. Very few exploration has been performed on the solution processable OLED based on deep/pure blue HLCT emitters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, many HLCT-based deep/ pure blue materials have been developed recently. [29][30][31][32][33][34][35][36][37][38][39][40][41][42] However, most of these emitters were utilized in OLED via vacuum deposition method. Very few exploration has been performed on the solution processable OLED based on deep/pure blue HLCT emitters.…”
Section: Introductionmentioning
confidence: 99%
“…[41] Furthermore, the EQE max of deep-blue HLCT emitters rarely reaches 10% and is difficult to meet the practical requirements. [40] Moreover, only few acceptor fragments, e.g., phenanthro [9,10-d]-imidazole and cyano, have been employed in HLCT molecules. [31,33,34] Therefore, there is still a large room to enrich the HLCT molecules as well as further improve their EL performance, especially in the deep blue cases.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, TADF with MR effect induced HOMO–LUMO separation has shown great potential to deliver a narrow EL band. 91–94 For example, Hatakeyama et al first reported two MR-TADF compounds with a B–N-containing core skeleton, which exhibited blue EL with a small FWHM of only 28 nm, a high maximum EQE max of 20.2%, and high color purity with CIE coordinates of (0.13, 0.09) which are close to the National Television System Committee (NTSC) blue light standard (CIE: (0.14, 0.08)). 95 The as-synthesized compounds with tert -butyl and carbazolyl units were subsequently modified and achieved blue OLEDs with a FWHM of only 27 nm, a high EQE max of 32.1%, and low efficiency roll-off.…”
Section: Application Of Pure Organic Rtp and Tadf Emitters In Electro...mentioning
confidence: 95%
“…HLCT or hot exciton mechanisms can also be used to upconvert triplet excitons into singlet excitons within the ns scale time range. [37][38][39][40][41][42][43][44] High-lying excited states can contribute to the quick exciton conversion, providing high external quantum efficiency (EQE) over 10% in the nondoped blue OLEDs. However, the exciton utilization efficiency (EUE) of the devices operated by the hot exciton mechanism needs to be further enhanced to reach a high EQE.…”
Section: Doi: 101002/adom202200256mentioning
confidence: 99%